A Prospective Study of Magnesium and Iron Intake and Pancreatic Cancer in Men - Kesavan, Yamini (Oxford University Press, 2010)
Many studies have investigated the relation between magnesium and iron intake and diabetes and, separately, between diabetes and pancreatic cancer. However, no known study has examined the direct association of magnesium and iron intake with pancreatic cancer risk. The authors obtained magnesium and iron intake data using food frequency questionnaires from the US male Health Professionals Follow-up Study, which began in 1986. During 851,476 person-years and 20 years of follow-up, 300 pancreatic cancer cases were documented. Cox proportional hazards models were used to estimate relative risks, adjusting for age, smoking, and body mass index. No associations were observed between magnesium or iron intake and pancreatic cancer (highest vs. lowest quintile: relative risk (RR) = 0.94, 95% confidence interval (CI): 0.66, 1.32 and RR = 0.93, 95% CI: 0.65, 1.34, respectively). Similarly, iron or magnesium supplement use was not related to pancreatic cancer. A statistically significant inverse relation was noted between magnesium and pancreatic cancer for subjects with a body mass index of ≥25 kg/m(2) (RR = 0.67, 95% CI: 0.46, 0.99; P-trend = 0.04). Although, overall, no relation between magnesium or iron intake and pancreatic cancer was observed in this cohort of men, an inverse association with magnesium was suggested among overweight individuals, which should be examined in other studies.